PERLINDUNGAN HAK CIPTA TERHADAP ASET DIGITAL NFT - Yenny Permata Liegestu; Tan, David (Maleo Law Journal, 2022)
NFT is the new tech-related trend. It is also predicted to become the new platform where artists can freely sell their art in any form. However, it is not as simple as that. As a trend, its popularity is increasing tremendously, where the good comes with the bad. One to mention, is the copyright infringement issue. The minting process or we can say, to produce the NFT is an easy process where it doesn’t even need an identification process of the real copyright owner. As a proof, there are many cases where traditional artists found a NFT based on their work with 100% similarity. For research in this writing, using normative research methods, which are based on written regulations, literature study that examine aspects of theory and legal explanations. The results of study indicate that law specializing in NFT hasn’t been formed yet, especially in Indonesia. The writer hopes that with this writing, readers can understand NFT more and at the same time how important this copyright issue is. Keywords : NFT, Copyright